2021
DOI: 10.1155/2021/5891095
|View full text |Cite
|
Sign up to set email alerts
|

The Health Hazards of Volcanoes: First Evidence of Neuroinflammation in the Hippocampus of Mice Exposed to Active Volcanic Surroundings

Abstract: Neuroinflammation is a process related to the onset of neurodegenerative diseases; one of the hallmarks of this process is microglial reactivation and the secretion by these cells of proinflammatory cytokines such as TNFα. Numerous studies report the relationship between neuroinflammatory processes and exposure to anthropogenic air pollutants, but few refer to natural pollutants. Volcanoes are highly inhabited natural sources of environmental pollution that induce changes in the nervous system, such as reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
1
1
0
Order By: Relevance
“…On the other hand, the microglial population was also increased in these animals and reactive forms of microglia were found in the same region of the hippocampus. Likewise, we also observed an increase in the pro-inflammatory cytokine TNFα inside some neurons in the subgranular area of the dentate gyrus as well as in the polymorphic region (Navarro-Sempere et al, 2021a ).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, the microglial population was also increased in these animals and reactive forms of microglia were found in the same region of the hippocampus. Likewise, we also observed an increase in the pro-inflammatory cytokine TNFα inside some neurons in the subgranular area of the dentate gyrus as well as in the polymorphic region (Navarro-Sempere et al, 2021a ).…”
Section: Introductionsupporting
confidence: 60%
“…As noted above, the existence of this neuroinflammatory environment in the mice captured in the village of Furnas may be expressing MTs not only in response to heavy metals, but also to the neuroinflammation caused by other volcanic pollutants with which they coexist. The animals in the reference area (Rabo de Peixe) are not exposed to these other pollutants either, so, as Navarro-Sempere et al, 2021a reported, they did not show neuroinflammatory processes and, therefore, did not show an increase in MT expression.…”
Section: Discussionmentioning
confidence: 86%